Experimenting Hybrid Justice in the Central African Republic: The Special Criminal Court, an Embodiment of Retributive Justice? - Nde Nyambi, Nfor (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2024)
This paper examines the Special Criminal Court (SCC) of the Central African Republic, focusing on its role in the country’s transitional justice framework. Established in 2015, the SCC plays a pivotal role in the country’s transitional justice process. While the Court’s Organic Law leans toward retributive justice, it also envisions reparations for victims. The SCC’s Rules and the country’s Criminal Procedure Law support the Court’s power to issue reparations orders through the “parties civiles” system. Through a doctrinal approach, utilizing textual analysis of case rulings and decisions, the study evaluates the Court’s capacity to offer justice to victims and its effectiveness in awarding reparations. The research highlights key decisions, including the June 16, 2023 judgment that granted financial reparations to victims, the October 23, 2023 ruling on individual and symbolic reparations, and the March 25, 2024 rejection of collective reparations due to cultural opposition from victims. The paper discusses the Court’s challenges in balancing retributive justice with restorative measures, emphasizing the need for external support due to the indigence of the convicted. Findings suggest that while the SCC has made strides in reparations, its capacity to fully realize restorative justice is hindered by financial limitations and procedural challenges. The paper concludes with recommendations to enhance the SCC’s reparative mandate through broader international cooperation.